The Potential of Glutinous Rice Tape Added with Lactobacillus plantarum Dad-13 and Saccharomyces boulardii as a Probiotic Food - Yulianto, Wisnu Adi; Pujimulyani, Dwiyati; Pratami, Candrika Ayu (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2022)
Glutinous rice tape circulating in the community generally does not contain probiotic cells. However, adding Lactobacillus plantarum Dad-13 and Saccharomyces boulardii can increase its potential as a probiotic food. This study is aimed to determine the effect of using glutinous rice varieties and the addition of probiotic cells on the number of lactic acid bacteria (LAB) and yeast, levels of anthocyanins, antioxidant activity, as well as the preference level of glutinous rice tape produced. A completely randomized design with a factorial pattern was used in this study. The first factor was glutinous rice varieties (white and black), while the second was the probiotic inoculum type (Lactobacillus plantarum Dad 13 and Saccharomyces boulardii) which were added simultaneously or individually. The result show that adding the probiotic cells simultaneously or individually in the production of white and black glutinous rice tape increased the LAB amount by 2 log cycles and yeast by 1 log cycle. The addition of Saccharomyces boulardii together with Lactobacillus plantarum Dad-13, or individually, resulted in higher anthocyanin levels in black glutinous rice tape than white glutinous tape. The antioxidant activity of white glutinous rice tape was improved by the addition of probiotic cells. For the black glutinous rice tape, the antioxidant activity (87.57-88.61 %RSA) was higher than the activity of white glutinous rice tape (15.58-51.22 %RSA). Furthermore, adding Lactobacillus plantarum Dad-13 simultaneously with Saccharomyces boulardii increased the preference level on aroma, color, taste, texture, and overall, and produced the white glutinous rice tape that the panelists most favored.